Silver-copper alloy wire for slip ring brush and its application
By using the combination of Ag, Cu, Ni, C and trace elements, combined with graphene-coated copper powder technology, silver-copper alloy wire for slip ring brushes with excellent performance was prepared, and the conductivity and hardness in the existing technology were solved. and the problem of insufficient service life, efficient signal transmission and long-life slip ring brush applications are achieved.
Patent Information
- Application Number
- CN202411365715.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-29
AI Technical Summary
The existing silver-copper alloy wires for slip ring brushes have insufficient conductivity, hardness, elasticity and service life, which cannot meet the requirements of humanoid robots and micro-electronic rotating devices for miniaturization and performance stability.
Using Ag, Cu, Ni and C as the main elements, and combinations of trace elements such as Ir, Pt, Rh, Ru, W, Re, Fe, V, etc. C is added in the form of graphene-coated copper powder, and is melted and atomized. , sintering, hot extrusion, cold rolling, heat treatment and drawing processes to prepare silver-copper alloy wires.
It significantly improves the conductivity, wear resistance, yield strength of silver-copper alloy wires at room temperature and high temperature, extends the service life, and has better performance than similar alloys on the market, and significantly improves signal transmission stability and reliability.
Smart Images

Figure CN118880098B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of conductive materials, and in particular relates to a silver-copper alloy wire for a slip ring brush and application thereof. Background Art
[0002] Slip rings and brushes are electrical components that connect rotating bodies and transmit power and signals. They are often called conductive slip rings, brushes, adapters, collector rings, collectors, rotary joints, collector rings, return rings, commutators, etc. They are precision transmission devices that realize the transmission of current, data signals or images and power between two relatively rotating mechanisms. Slip rings are usually installed at the rotation center of the equipment and are mainly composed of two parts: rotating and stationary. The rotating part is connected to the rotating structure of the equipment and rotates with it, which is called the "rotor", and the stationary part is connected to the fixed structure of the equipment, which is called the "stator".
[0003] At present, the silver-copper alloy wires used in slip ring brushes at home and abroad are mainly silver-copper binary alloys and silver-copper-nickel ternary alloys, and their specific compositions are: 90 wt.% Ag and 10 wt.% Cu; 85 wt.% Ag and 15 wt.% Cu; 72 wt.% Ag and 28 wt.% Cu; 78 wt.% Ag, 20 wt.% Cu and 2 wt.% Ni; 74 wt.% Ag, 25 wt.% Cu and 1 wt.% Ni; Some literatures also reported adding Zn, B, Cr, Sn, Cd, graphite powder, molybdenum disulfide and other elements to the basic components of silver-copper-nickel ternary alloys. However, its comprehensive performance is still poor, mainly manifested in insufficient conductivity, hardness, elasticity, material performance stability and service life. With the changes in the application scenarios of slip ring brush system devices, such as humanoid robots and some micro-electronic rotating devices, requirements are put forward for the miniaturization of slip ring brush components, and at the same time, higher requirements are put forward for the performance stability of materials used for slip ring brushes. However, the existing commercially available silver-copper alloy and silver-copper-nickel alloy system brush wires cannot meet the above requirements.
[0004] Therefore, there is an urgent need for a silver-copper alloy wire for slip ring brushes whose conductivity, elasticity, room temperature and high temperature yield strength, wear resistance and service life are much higher than similar commercially available alloys to solve the above problems. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes a silver-copper alloy wire for slip ring brushes and its application. The silver-copper alloy wire for slip ring brushes provided by the present invention has excellent conductivity, elasticity, yield strength at room temperature and high temperature, wear resistance, and long service life.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The invention provides a silver-copper alloy wire for a slip ring brush, comprising main elements and trace elements; the main elements include Ag, Cu, Ni and C, the trace elements include one or more of Ir, Pt, Rh, Ru, W, Re, Fe and V; the C is added in the form of graphene-coated copper powder.
[0008] Preferably, in terms of weight percentage of the total alloy raw materials, the main elements include Ag: 73-75 wt.%, Cu: 24-26 wt.%, Ni: 0.2-0.7 wt.% and C: 0.001-0.05 wt.%.
[0009] Preferably, the trace elements include one or more of Ir: 0.05-0.5Wt.%, Pt: 0.05-0.5Wt.%, Rh: 0.05-0.5Wt.%, Ru: 0.05-0.5Wt.%, W: 0.05-0.5Wt.%, Re: 0.05-0.5Wt.%, Fe: 0.05-0.5Wt.% and V: 0.05-0.5Wt.%, calculated as a percentage by weight of the total alloy raw materials.
[0010] Preferably, in terms of weight percentage, the silver-copper alloy wire for the slip ring brush includes Ag: 73-75Wt.%, Cu: 24-26Wt.%, Ni: 0.2-0.7Wt.%, C: 0.001-0.05Wt.%, Ir: 0.05-0.5Wt.%, W: 0.05-0.5Wt.% and V: 0.05-0.5Wt.%.
[0011] Preferably, the diameter of the silver-copper alloy wire for the slip ring brush is 0.01 mm-0.8 mm.
[0012] Preferably, the method for preparing the silver-copper alloy wire for the slip ring brush comprises the following steps:
[0013] (1) Cu, Ni and trace elements are made into a CuNiM master alloy, and then Ag and the CuNiM master alloy are mixed, and the mixture is smelted and atomized to obtain an AgCuNiM alloy powder;
[0014] (2) C in the form of graphene-coated copper powder is mixed with the AgCuNiM alloy powder obtained in step (1), and then sintered, hot extruded, cold rolled, heat treated, cold drawn, peeled and drawn to obtain the silver-copper alloy wire for the slip ring brush.
[0015] Preferably, in step (2), the sintering temperature is 200-750°C, the holding time is 45-90 min, the pressure is 200-2000 KN, and the vacuum degree is less than 3×10 -3 Pa.
[0016] Preferably, in step (2), the hot extrusion temperature is 600-750° C., and the holding time is 90-120 min.
[0017] Preferably, in step (2), the heat treatment temperature is 400-700°C, the holding time is 60-90 min, and the vacuum degree is less than 3×10 -3 Pa.
[0018] The present invention also provides the application of the silver-copper alloy wire for slip ring brushes described in the above technical solution in slip ring brushes.
[0019] Compared with the prior art, the present invention has the following advantages and technical effects:
[0020] The silver-copper alloy wire for slip ring brushes provided by the present invention consists of main elements Ag, Cu, Ni, C and one or more elements of trace elements Ir, Pt, Rh, Ru, W, Re, Fe, and V, and C is added in the form of graphene-coated copper powder. The conductivity, wear resistance, elasticity, yield strength at room temperature and high temperature, and service life of the obtained silver-copper alloy wire for slip ring brushes are much higher than those of similar commercially available alloys.
[0021] The silver-copper alloy wire for the slip ring brush provided by the present invention has an electrical conductivity of >75%IACS, a microhardness of >195HV, an elastic modulus of >90GPa, a yield strength of >700MPa at room temperature 25°C, a yield strength of >650MPa at 250°C, and a service life of more than 11 million revolutions (paired with a gold-plated copper ring with a diameter of 45mm). When the service life reaches a maximum of 14 million revolutions, the yield strength of the material remains almost unchanged, thereby ensuring stable signal transmission between the slip ring and the brush wire. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0023] Figure 1 The process flow chart of the preparation method of the silver-copper alloy wire for the slip ring brush of the present invention;
[0024] Figure 2 It is a schematic diagram of testing the service life of the silver-copper alloy wire used in the slip ring brush of the present invention. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0027] An embodiment of the present invention provides a silver-copper alloy wire for a slip ring brush, comprising main elements and trace elements; the main elements include Ag, Cu, Ni and C, the trace elements include one or more of Ir, Pt, Rh, Ru, W, Re, Fe and V; the C is added in the form of graphene-coated copper powder.
[0028] The present invention uses Ag, Cu, Ni and C as main elements, wherein Ag plays the role of conducting electricity and supporting the alloy matrix, Cu plays the role of strengthening the alloy and increasing the hardness, and Ni plays the role of further strengthening the alloy. At the same time, the C element is added in the form of graphene-coated copper powder, which can not only strengthen the alloy, but also greatly reduce the friction coefficient between the silver-copper alloy wire and the friction pair during use, thereby improving the wear resistance and service life of the silver-copper alloy wire.
[0029] In a preferred embodiment, the main elements include Ag: 73-75 wt.%, Cu: 24-26 wt.%, Ni: 0.2-0.7 wt.% and C: 0.001-0.05 wt.%, based on the weight percentage of the total alloy raw materials.
[0030] The present invention adds trace elements on the basis of the main elements to strengthen the alloy, especially to improve the elasticity, room temperature and high temperature yield strength of the material, reduce the contact resistance and friction coefficient between the friction pair, and thus improve the signal transmission stability and reliability, wear resistance and service life between the friction pair. The present invention improves the room temperature and high temperature yield strength of the silver-copper alloy wire, thereby improving the signal transmission stability and reliability of the silver-copper alloy wire under high temperature use conditions.
[0031] In a preferred embodiment, the trace elements include one or more of Ir: 0.05-0.5Wt.%, Pt: 0.05-0.5Wt.%, Rh: 0.05-0.5Wt.%, Ru: 0.05-0.5Wt.%, W: 0.05-0.5Wt.%, Re: 0.05-0.5Wt.%, Fe: 0.05-0.5Wt.% and V: 0.05-0.5Wt.%, calculated as a percentage by weight of the total alloy raw materials.
[0032] In a preferred embodiment, the silver-copper alloy wire for the slip ring brush includes, by weight percentage, Ag: 73-75Wt.%, Cu: 24-26Wt.%, Ni: 0.2-0.7Wt.%, C: 0.001-0.05Wt.%, Ir: 0.05-0.5Wt.%, W: 0.05-0.5Wt.% and V: 0.05-0.5Wt.%.
[0033] In a preferred embodiment, the diameter of the silver-copper alloy wire for the slip ring brush is 0.01 mm-0.8 mm, more preferably 0.15-0.8 mm.
[0034] In a preferred embodiment, the method for preparing the silver-copper alloy wire for the slip ring brush is shown in the process flow chart. Figure 1 , including the following steps:
[0035] (1) Cu, Ni and trace elements are made into a CuNiM master alloy, and then Ag and the CuNiM master alloy are mixed, and the mixture is smelted and atomized to obtain an AgCuNiM alloy powder;
[0036] (2) C in the form of graphene-coated copper powder is mixed with the AgCuNiM alloy powder obtained in step (1), and then sintered, hot extruded, cold rolled, heat treated, cold drawn, peeled and drawn to obtain the silver-copper alloy wire for the slip ring brush.
[0037] In a preferred embodiment, in step (1), the preparation method of the CuNiM master alloy is: smelting and casting Cu, Ni and trace elements to obtain the CuNiM master alloy.
[0038] In a preferred embodiment, the melting times are 2 times, and the vacuum degree is less than 3×10 -3 Pa, the equipment is an induction melting furnace.
[0039] In a preferred embodiment, the CuNiM master alloy is cylindrical in shape with a diameter of 70 mm.
[0040] In a preferred embodiment, in step (1), the smelting and atomizing equipment is a vacuum induction melting-gas atomizing powder making equipment, and the atmosphere is N2 with a purity greater than 99.99%.
[0041] In a preferred embodiment, in step (1), the AgCuNiM alloy powder has a spherical and / or quasi-spherical shape, and a diameter of 0.005-0.07 mm, more preferably 0.025-0.07 mm.
[0042] In a preferred embodiment, in step (2), the graphene-coated copper powder has a spherical and / or quasi-spherical shape and a diameter of 0.005-0.07 mm; the amount of the graphene-coated copper powder is calculated based on the proportion of the C element in the silver-copper alloy wire; and the graphene-coated copper powder is purchased from Tanaka Corporation of Japan.
[0043] In a preferred embodiment, in step (2), the graphene-coated copper powder and the AgCuNiM alloy powder are mixed by ball milling; the ball milling equipment is a planetary ball mill, and the ball milling time is 10 hours.
[0044] In a preferred embodiment, in step (2), the sintering is vacuum hot pressing sintering; the sintering temperature is 200-750°C, more preferably 400-750°C; the sintering holding time is 45-90min, more preferably 60-90min; the sintering pressure is 200-2000KN, more preferably 200-700KN; the sintering vacuum degree is less than 3×10 -3 Pa; the diameter of the sintered ingot obtained by the sintering is 65-69 mm and the shape is cylindrical.
[0045] In a preferred embodiment, in step (2), the temperature of the hot extrusion is 600-750°C, more preferably 650-750°C; the holding time of the hot extrusion is 90-120min; the diameter of the silver-copper alloy rod obtained by the hot extrusion is 8-16mm; before the hot extrusion, the surface of the sintered ingot obtained by sintering is coated with graphite emulsion with a purity greater than 99.99% and the coating thickness is 0.5-1mm.
[0046] In a preferred embodiment, in step (2), the deformation amount of the cold rolling pass is less than 20%; and the diameter of the cold-rolled bar obtained by the cold rolling is 2.5-8 mm.
[0047] In a preferred embodiment, in step (2), the temperature of the heat treatment is 400-700°C, more preferably 500-700°C; the holding time of the heat treatment is 60-90 min, more preferably 70-90 min; the vacuum degree of the heat treatment is less than 3×10 -3 Pa; the cooling method of the heat treatment is furnace cooling.
[0048] In a preferred embodiment, in step (2), the cold drawing has a deformation amount of less than 15%; and the diameter of the alloy wire obtained after the cold drawing is 0.5-1 mm.
[0049] In a preferred embodiment, in step (2), the peeling is to remove the surface thickness of the alloy wire after cold drawing by 0.01 mm; the diameter of the alloy wire obtained by peeling is 0.48-0.98 mm.
[0050] In a preferred embodiment, in step (2), the drawing deformation of each drawing pass is less than 10%; and the diameter of the alloy wire obtained by drawing is 0.01-0.8 mm.
[0051] The present invention also provides the application of the silver-copper alloy wire for slip ring brushes described in the above technical solution in slip ring brushes.
[0052] Unless otherwise specified, the elements in the embodiments of the present invention are added in the form of simple substances.
[0053] The room temperature in the embodiments of the present invention refers to "25±2°C".
[0054] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.
[0055] Example 1
[0056] A silver-copper alloy wire for a slip ring brush, comprising the following components by weight percentage:
[0057] Ag: 75Wt.%, Cu: 24Wt.%, Ni: 0.5Wt.%, C: 0.05Wt.%, Ir: 0.05Wt.%, W: 0.25Wt.% and V: 0.15Wt.%.
[0058] Preparation process of silver-copper alloy wire for slip ring brushes (taking 1000 grams of alloy as an example):
[0059] (1) According to the above composition ratio, calculate the weight of each element required for 1000 g of silver-copper alloy wire: Ag is 750 g, Cu is 160 g (240×2 / 3=160 g), Ni is 5 g, graphene-coated copper powder is 80.5 g (the content of graphene in the graphene-coated copper powder is 0.5 g, and the content of Cu is 240×1 / 3=80 g), Ir is 0.5 g, W is 2.5 g, and V is 1.5 g.
[0060] (2) Place 160 g of Cu, 5 g of Ni, 0.5 g of Ir, 2.5 g of W and 1.5 g of V (a total of 169.5 g) in a zirconia copper crucible in an induction melting furnace, close the furnace door, and evacuate to a vacuum degree of <3×10 -3 Pa, smelting is carried out, and after the melt is cooled, the smelting is repeated once, and then it is cast in a graphite mold with a diameter of 70 mm. After cooling and taking out of the furnace, a CuNiM intermediate alloy with a weight of 169.5 grams is obtained.
[0061] (3) 169.5 g of the CuNiM master alloy obtained in step (2) and 750 g of Ag are placed in a graphite crucible of a vacuum induction melting-gas atomization powder making device, and subjected to induction melting and N2 atomization to obtain AgCuNiM alloy powder with a diameter of 0.025-0.07 mm and a spherical or quasi-spherical shape; wherein the purity of N2 is greater than 99.99%.
[0062] (4) The AgCuNiM alloy powder obtained in step (3) and 80.5 g of graphene-coated copper powder C@Cu were mixed in a planetary ball mill for 10 h, and then the uniform mixed powder was loaded into a graphite mold with a diameter of 69 mm for hot pressing and sintering to obtain a sintered body with a diameter of 65-69 mm; the process parameters of hot pressing and sintering were: vacuum degree <3×10 -3 Pa, temperature 600℃, holding time 60min, pressure 700KN.
[0063] (5) The surface of the sintered body obtained in step (4) is coated with graphite emulsion with a thickness of 0.5-1 mm and a purity greater than 99.99%, and then kept at 650° C. in a resistance furnace for 90 min, and then extruded into a silver-copper alloy rod with a diameter of 10 mm on a horizontal extruder.
[0064] (6) The silver-copper alloy rod obtained in step (5) is cold rolled with a deformation amount of less than 20% per pass to obtain a silver-copper alloy rod with a diameter of 3.5 mm.
[0065] (7) The silver-copper alloy rod obtained in step (6) is subjected to intermediate vacuum heat treatment in a vacuum heat treatment furnace, and the vacuum degree is less than 3×10 -3 Pa, 500℃ for 90min, cooled with the furnace to obtain the heat-treated silver-copper alloy rod.
[0066] (8) The silver-copper alloy rod obtained after heat treatment in step (7) is cold drawn with a deformation amount of less than 15% per pass to obtain a silver-copper alloy wire with a diameter of 0.8 mm.
[0067] (9) Repeat steps (7) and (8) to obtain a silver-copper alloy wire with a diameter of 0.6 mm.
[0068] (10) The silver-copper alloy wire obtained in step (9) is peeled to remove 0.01 mm of surface thickness to obtain a silver-copper alloy wire with a diameter of 0.58 mm.
[0069] (11) The silver-copper alloy wire obtained in step (10) is drawn with a deformation amount of less than 10% per drawing pass, and after multiple drawing passes, a silver-copper alloy finished wire with a diameter of 0.25 mm is obtained, which is the silver-copper alloy wire for slip ring brushes.
[0070] Example 2
[0071] A silver-copper alloy wire for a slip ring brush, comprising the following components by weight percentage:
[0072] Ag: 75Wt.%, Cu: 24Wt.%, Ni: 0.65Wt.%, C: 0.05Wt.%, Ir: 0.05Wt.%, W: 0.25Wt.%.
[0073] Preparation process of silver-copper alloy wire for slip ring brushes (taking 5000 grams of alloy as an example):
[0074] (1) According to the above composition ratio, calculate the weight of each element required for 5000 g of silver-copper alloy wire: Ag is 3750 g, Cu is 800 g (1200×2 / 3=800 g), Ni is 32.5 g, graphene-coated copper powder is 402.5 g (the content of graphene in the graphene-coated copper powder is 2.5 g, and the content of Cu is 1200×1 / 3=400 g), Ir is 2.5 g, and W is 12.5 g.
[0075] (2) Place 800 g of Cu, 32.5 g of Ni, 2.5 g of Ir and 12.5 g of W (a total of 847.5 g) in a zirconia copper crucible in an induction melting furnace, close the furnace door, and evacuate the furnace to a vacuum degree of <3 × 10 -3 Pa, smelting is carried out, and after the melt is cooled, the smelting is repeated once, and then it is cast in a graphite mold with a diameter of 70 mm. After cooling and taking out of the furnace, a CuNiM intermediate alloy with a weight of 847.5 grams is obtained.
[0076] (3) 847.5 g of the CuNiM master alloy obtained in step (2) and 3750 g of Ag are placed in a graphite crucible of a vacuum induction melting-gas atomization powder making device, and subjected to induction melting and N2 atomization to obtain AgCuNiM alloy powder with a diameter of 0.025-0.07 mm and a spherical or quasi-spherical shape; wherein the purity of N2 is greater than 99.99%.
[0077] (4) The AgCuNiM alloy powder obtained in step (3) and 402.5 g of graphene-coated copper powder C@Cu were mixed in a planetary ball mill for 10 h, and then the uniform mixed powder was loaded into a graphite mold with a diameter of 69 mm for hot pressing and sintering to obtain a sintered body with a diameter of 65-69 mm; the process parameters of hot pressing and sintering were: vacuum degree <3×10 -3 Pa, temperature 400℃, holding time 90min, pressure 2000KN.
[0078] (5) The surface of the sintered body obtained in step (4) is coated with graphite emulsion with a thickness of 0.5-1 mm and a purity greater than 99.99%, and then kept at 600° C. in a resistance furnace for 120 min, and then extruded into a silver-copper alloy rod with a diameter of 16 mm on a horizontal extruder.
[0079] (6) The silver-copper alloy rod obtained in step (5) is cold rolled with a deformation amount of less than 20% per pass to obtain a silver-copper alloy rod with a diameter of 8 mm.
[0080] (7) The silver-copper alloy rod obtained in step (6) is subjected to intermediate vacuum heat treatment in a vacuum heat treatment furnace, and the vacuum degree is less than 3×10 -3 Pa, keep warm at 400℃ for 90min, cool with the furnace, and obtain the heat-treated silver-copper alloy rod.
[0081] (8) The silver-copper alloy rod obtained after heat treatment in step (7) is cold drawn with a deformation amount of less than 15% per pass to obtain a silver-copper alloy wire with a diameter of 3 mm.
[0082] (9) Repeat steps (7) and (8) to obtain a silver-copper alloy wire with a diameter of 1 mm.
[0083] (10) The silver-copper alloy wire obtained in step (9) is peeled to remove 0.01 mm of surface thickness to obtain a silver-copper alloy wire with a diameter of 0.98 mm.
[0084] (11) The silver-copper alloy wire obtained in step (10) is drawn with a deformation amount of less than 10% per drawing pass, and after multiple drawing passes, a silver-copper alloy finished wire with a diameter of 0.8 mm is obtained, namely, the silver-copper alloy wire for slip ring brushes.
[0085] Example 3
[0086] A silver-copper alloy wire for a slip ring brush, comprising the following components by weight percentage:
[0087] Ag: 75Wt.%, Cu: 24Wt.%, Ni: 0.6Wt.%, C: 0.05Wt.%, Ir: 0.05Wt.% and Re: 0.3Wt.%.
[0088] Preparation process of silver-copper alloy wire for slip ring brushes (taking 2000 grams of alloy as an example):
[0089] (1) According to the above composition ratio, calculate the weight of each element required for 2000 g of silver-copper alloy wire: Ag is 1500 g, Cu is 320 g (480×2 / 3=320 g), Ni is 12 g, graphene-coated copper powder is 161 g (the content of graphene in the graphene-coated copper powder is 1 g, and the content of Cu is 480×1 / 3=160 g), Ir is 1 g, and Re is 6 g.
[0090] (2) Place 320 g of Cu, 12 g of Ni, 1 g of Ir and 6 g of Re (339 g in total) in a zirconia copper crucible in an induction melting furnace, close the furnace door, and evacuate to a vacuum degree of <3×10-3 Pa, smelting is carried out, and after the melt is cooled, the smelting is repeated once, and then it is cast in a graphite mold with a diameter of 70 mm. After cooling and taking out of the furnace, a CuNiM intermediate alloy with a weight of 339 grams is obtained.
[0091] (3) 339 g of the CuNiM master alloy obtained in step (2) and 1500 g of Ag are placed in a graphite crucible of a vacuum induction melting-gas atomization powder making device, and subjected to induction melting and N2 atomization to obtain AgCuNiM alloy powder with a diameter of 0.025-0.07 mm and a spherical or quasi-spherical shape; wherein the purity of N2 is greater than 99.99%.
[0092] (4) The AgCuNiM alloy powder obtained in step (3) and 161 g of graphene-coated copper powder C@Cu were mixed in a planetary ball mill for 10 h, and then the uniform mixed powder was loaded into a graphite mold with a diameter of 69 mm for hot pressing and sintering to obtain a sintered body with a diameter of 65-69 mm; the process parameters of hot pressing and sintering were: vacuum degree <3×10 -3 Pa, temperature 750℃, holding time 45min, pressure 200KN.
[0093] (5) The surface of the sintered body obtained in step (4) is coated with graphite emulsion with a thickness of 0.5-1 mm and a purity greater than 99.99%, and then kept at 750° C. in a resistance furnace for 90 min, and then extruded into a silver-copper alloy rod with a diameter of 8 mm on a horizontal extruder.
[0094] (6) The silver-copper alloy rod obtained in step (5) is cold rolled with a deformation amount of less than 20% per pass to obtain a silver-copper alloy rod with a diameter of 2.5 mm.
[0095] (7) The silver-copper alloy rod obtained in step (6) is subjected to intermediate vacuum heat treatment in a vacuum heat treatment furnace, and the vacuum degree is less than 3×10 -3 Pa, keep warm at 700℃ for 90min, cool with the furnace to obtain the heat-treated silver-copper alloy rod.
[0096] (8) The silver-copper alloy rod obtained after heat treatment in step (7) is cold drawn with a deformation amount of less than 15% per pass to obtain a silver-copper alloy wire with a diameter of 0.7 mm.
[0097] (9) Repeat steps (7) and (8) to obtain a silver-copper alloy wire with a diameter of 0.5 mm.
[0098] (10) The silver-copper alloy wire obtained in step (9) is peeled to remove 0.01 mm of surface thickness to obtain a silver-copper alloy wire with a diameter of 0.48 mm.
[0099] (11) The silver-copper alloy wire obtained in step (10) is drawn with a deformation amount of less than 10% per drawing pass, and after multiple drawing passes, a finished silver-copper alloy wire with a diameter of 0.15 mm is obtained, namely, the silver-copper alloy wire for slip ring brushes.
[0100] Example 4-21
[0101] The composition of the silver-copper alloy wire for the slip ring brush in Example 4-21 is shown in Table 1, and the preparation steps and process parameters are the same as those in Example 1.
[0102] Comparative Example 1
[0103] The commercially available ternary silver-copper-nickel alloy wire (0.25 mm in diameter) consists of 78% Ag, 20% Cu and 2% Ni by mass percentage.
[0104] Comparative Example 2
[0105] The commercially available ternary silver-copper-nickel alloy wire (0.25 mm in diameter) consists of 74% Ag, 25% Cu and 1% Ni by mass percentage.
[0106] Table 1 Composition of the silver-copper alloy wire for slip ring brushes in Examples 1-21
[0107]
[0108] See the service life test diagram Figure 2 The performance measurement results of the silver-copper alloy in Examples 1-21 and Comparative Examples 1-2 are shown in Table 2.
[0109] Table 2 Properties of silver-copper alloys in Examples 1-21 and Comparative Examples 1-2
[0110]
[0111] It can be seen from Table 2 that the silver-copper alloy wire provided by the present invention has an electrical conductivity of >75%IACS, a microhardness of >195HV, an elastic modulus of >90GPa, a yield strength at room temperature of 25°C of >700MPa, a yield strength at 250°C of >650MPa, and a service life of >11 million revolutions, and its performance is significantly better than that of the commercially available ternary silver-copper-nickel alloy wire.
[0112] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A silver-copper alloy wire for a slip ring brush, characterized in that: It comprises main elements and trace elements; the main elements comprise Ag, Cu, Ni and C, the trace elements comprise one or more of Ir, Pt, Rh, Ru, W, Re, Fe and V; the C is added in the form of graphene-coated copper powder; in terms of weight percentage of the total raw materials of the alloy, the main elements comprise Ag: 73-75Wt.%, Cu: 24-26Wt.%, Ni: 0.2-0.7Wt.% and C: 0.001-0.05Wt.%; The method for preparing the silver-copper alloy wire for the slip ring brush comprises the following steps: (1) Cu, Ni and trace elements are made into a CuNiM master alloy, and then Ag and the CuNiM master alloy are mixed, and the mixture is smelted and atomized to obtain AgCuNiM alloy powder; (2) C in the form of graphene-coated copper powder is mixed with the AgCuNiM alloy powder obtained in step (1), and then sintered, hot extruded, cold rolled, heat treated, cold drawn, peeled and drawn to obtain the silver-copper alloy wire for slip ring brush; the hot extrusion temperature is 600-750°C, the holding time is 90-120min; the heat treatment temperature is 500-700°C, the holding time is 60-90min, and the vacuum degree is less than 3×10 -3 Pa.
2. The silver-copper alloy wire for slip ring brush according to claim 1, characterized in that: Calculated by weight percentage of the total alloy raw materials, the trace elements include one or more of Ir: 0.05-0.5Wt.%, Pt: 0.05-0.5Wt.%, Rh: 0.05-0.5Wt.%, Ru: 0.05-0.5Wt.%, W: 0.05-0.5Wt.%, Re: 0.05-0.5Wt.%, Fe: 0.05-0.5Wt.% and V: 0.05-0.5Wt.%.
3. The silver-copper alloy wire for slip ring brush according to claim 1, characterized in that: In terms of weight percentage, the silver-copper alloy wire for the slip ring brush includes Ag: 73-75Wt.%, Cu: 24-26Wt.%, Ni: 0.2-0.7Wt.%, C: 0.001-0.05Wt.%, Ir: 0.05-0.5Wt.%, W: 0.05-0.5Wt.% and V: 0.05-0.5Wt.%.
4. The silver-copper alloy wire for slip ring brush according to claim 1, characterized in that: The diameter of the silver-copper alloy wire used for the slip ring brush is 0.01mm-0.8mm.
5. The silver-copper alloy wire for slip ring brush according to claim 1, characterized in that: In step (2), the sintering temperature is 200-750°C, the holding time is 45-90 min, the pressure is 200-2000 kN, and the vacuum degree is less than 3×10 -3 Pa.
6. Use of the silver-copper alloy wire for slip ring brushes according to any one of claims 1 to 5 in slip ring brushes.
